Robust control in water management - Roseta-Palma, C. (2002)
Since surface water ‡ows are often stochastic, there is a role to be played by groundwater or surface reservoirs in protecting users against uncertainty. In most of the literature, the word “uncertainty” means the realization of an event whose true probability distribution is known. Pure uncertainty, where the state space of outcomes is known but one is unable to assign probabilities, has largely been ignored. When the decision maker is unsure about his model, in the sense that there is a range of approximate models that he also considers as possibly true, the problem is one of robust dynamic control. The purpose of our work is to analyse water storage and use decisions in a robust framework. Uncertainty about the behaviour of precipitation is introduced, and the implications for water use are presented. Robust choices are compared with those of a benchmark stochastic model and the emergence of precautionary behaviour is discussed.